A new protocol for exercise testing in COPD; improved prediction algorithm for WMAX and validation of the endurance test in a placebo-controlled double bronchodilator study. (September 2021) - Tufvesson, Ellen; Radner, Finn; Simonsen, Anton; Papapostolou, Georgia; Jarenbäck, Linnea; Jönsson, Saga; Nihlen, Ulf; Tunsäter, Alf; Ankerst, Jaro; Peterson, Stefan; Bjermer, Leif; Eriksson, Göran
Background: Two new protocols have been developed for bicycle exercise testing in chronic obstructive pulmonary disease (COPD) with an individualized cardiopulmonary exercise test (ICPET) and subsequent customized endurance test (CET), which generate less interindividual spread in endurance time compared with the standard endurance test. Main objectives of this study were to improve the prediction algorithm for WMAX for the ICPET and validate the CET by examining treatment effects on exercise performance of indacaterol/glycopyrronium (IND/GLY) compared with placebo. Methods: COPD patients, with forced expiratory volume in 1 s ( FEV1 ) 40–80% predicted, were recruited. Pooled baseline data from two previous studies ( n  = 38) were used for the development of an improved WMAX prediction algorithm. Additional COPD patients ( n  = 14) were recruited and performed the ICPET, using the new prediction formula at visit 1. Prior to the CET at visits 2 and 3, they were randomized to a single dose of IND/GLY (110/50 µg) or placebo. Results: The improved multiple regression algorithm for WMAX includes diffusing capacity for carbon monoxide ( DLCO ), FEV1, sex, age and height and correlated to measured WMAX ( R 2  = 0.89 and slope = 0.89). Treatment with IND/GLY showed improvement in endurance time versus placebo, mean 113 s [95% confidence interval (CI): 6–220], p  = 0.037, with more prominent effect in patients with FEV 1  < 70% predicted. Conclusion: The two new protocols for ICPET (including the new improved algorithm) and CET were retested with consistent results. In addition, the CET showed a significant and clinically relevant prolongation of endurance time for IND/GLY versus placebo in a small number of patients.